2019
DOI: 10.1029/2018rs006686
|View full text |Cite
|
Sign up to set email alerts
|

Critical Issues in Ionospheric Data Quality and Implications for Scientific Studies

Abstract: Ionospheric data are valuable records of the behavior of the ionosphere, solar activity, and the entire Sun-Earth system. The data are critical for both societally important services and scientific investigations of upper atmospheric variability. This work investigates some of the difficulties and pitfalls in maintaining long-term records of geophysical measurements. This investigation focuses on the ionospheric parameters contained in the historical data sets within the National Oceanic and Atmospheric Admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Ionosondes provide one of the longest-running and most reliable measurements of the ionosphere [1]. By scanning across a range of frequencies in the HF band and measuring the echo time of signals reflected from the ionosphere, they are capable of producing ionograms.…”
Section: Introductionmentioning
confidence: 99%
“…Ionosondes provide one of the longest-running and most reliable measurements of the ionosphere [1]. By scanning across a range of frequencies in the HF band and measuring the echo time of signals reflected from the ionosphere, they are capable of producing ionograms.…”
Section: Introductionmentioning
confidence: 99%
“…A complimentary assessment to benefit the quality indicators of GIM's accuracy would be the incorporation of ionosonde measurements as a reference to specify the "true" ionosphere. The electron density peak in the F 2 layer (N m F 2 ) is commonly measured by ionosondes in terms of the associated critical frequency (foF 2 ), which is specially trustable when they are directly provided from manually calibrated ionosonde datasets [16]. Some studies related to the estimation of foF 2 can be found in works such as Altinay et al [17] and Pietrella et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…Digisonde observations (Reinisch et al, 2009) over eight selected digisonde stations (AS00Q, GR13L, GU513, JI91J, LL721, LM42B, MHJ45, and SMK29 in Figure 5) located at low latitudes and midlatitudes during daytime from 14 September to 16 October 2019 are used to derive N m F 2 and h m F 2 ( F ‐peak altitude) (Reinisch & Galkin, 2011). Note that the N m F 2 and h m F 2 are acquired by manually scaling the ionograms to mitigate possible errors due to autoscaling (e.g., Araujo‐Pradere et al, 2019). In this study, a total of 1,465 digisonde observations is used to validate the peak density and altitude information from GIS.…”
Section: Validation With Digisonde Observationmentioning
confidence: 99%